Catalyst for photocatalytic degradation of acid red B, preparation method of catalyst and method for photocatalytic degradation of acid red B

By using a silicon source during the catalyst molding process to generate a viscous silica mesh and converting it into a silicon dioxide film, the problem of metal component loss is solved, extending the life of the catalyst and improving its activity.

CN119425765AActive Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310962189.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14
Estimated Expiration
2043-08-01

AI Technical Summary

Technical Problem

In the existing supported catalysts, metal components are easily lost during the reaction process, resulting in a shortening of the catalyst service life and a reduction in the catalytic effect.

Method used

By adding the raw material silicon source used to synthesize molecular sieve during the catalyst molding process, hydrolyzing to form a viscous silica net. The viscous silica net bonds the molecular sieve particles to each other and converts them into a silicon dioxide film under high-temperature calcination conditions, covering the molecular sieve sieve. On the outer surface, a protective film is formed to prevent metal loss.

Benefits of technology

It extends the life and activity of the catalyst, improves the mechanical strength of the molecular sieve, and effectively avoids the catalyst deactivation caused by agglomeration of metal particles at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425765A_ABST
    Figure CN119425765A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of molecular sieve preparation, and provides a preparation method of a catalyst for photocatalytic degradation of acid red B. The preparation method comprises the following steps: mixing SBA molecular sieve raw powder, a metal source, a first silicon source and an alkali solution to obtain a mixture, and molding and drying the mixture to obtain a molecular sieve A; wherein the metal source comprises at least one of a vanadium source and a titanium source; mixing an organic template agent R, water, a second silicon source and acid to obtain a solution B; and adding the solution B into the molecular sieve A, carrying out hydrothermal crystallization, filtering, washing, drying and roasting to obtain the catalyst for photocatalytic degradation of the acid red B. The preparation method provided by the invention is simple, and the prepared catalyst is covered with the silicon dioxide film outside the molecular sieve, so that metal active sites are not easy to lose in the reaction process. The invention also provides a catalyst for photocatalytic degradation of acid red B and a method for photocatalytic degradation of acid red B.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of molecular sieve preparation, and more specifically to a photocatalytic degradation catalyst for acid red B and a preparation method thereof, as well as a photocatalytic degradation method for acid red B. Background Art

[0002] Azo dyes are the main dyes used in the global leather industry and printing and dyeing industry, accounting for more than 50% of industrially used dyes. They have high chemical stability and are difficult to degrade, making them one of the main sources of water pollution. Although azo dyes themselves do not have direct carcinogenic effects, some of them are decomposed and reduced to some carcinogenic aromatic amines under the action of specific enzymes in the human body, posing a huge threat to human health. Acid red B (acid red B), also known as acid red B and acid red FB, is a representative one of them. The dye wastewater has the characteristics of sunlight resistance, good antioxidant properties, strong stability, deep chroma, poor biodegradability, carcinogenicity, and teratogenicity, which has always been a difficult problem in dye wastewater treatment.

[0003] Some people have tried to treat acid red B dye wastewater by physical adsorption, coagulation and sedimentation, electrochemical method, advanced oxidation method, wet hydrogen peroxide oxidation method, ultrasonic oxidation method, biological method, etc. The disadvantages of physical adsorption method are high cost, difficulty in cleaning and regenerating adsorbents, and insufficient adsorption of certain macromolecular dyes. The coagulation and sedimentation method has high operating costs, large amount of sludge and difficulty in dehydration, and poor treatment effect on hydrophilic dyes. The electrochemical method may produce alkaline substances and other toxic chemicals during the decolorization process of acid dyes. The raw material cost of the advanced oxidation method is high, and the pH generally needs to be adjusted after the reaction. The wet hydrogen peroxide oxidation method requires heating and pressurization conditions, which is costly and complicated to operate. The ultrasonic oxidation method has a slow oxidation rate and limited processing capacity. The screening of biological strains is difficult, and its chromaticity removal rate is also unsatisfactory. Among the many photocatalysts, Ti and V metals have become the mainstream materials for the current research on photocatalytic degradation of acid red B due to their excellent photocatalytic performance and relatively low cost.

[0004] The catalyst preparation method has a great influence on the properties of precious metal supported catalysts. However, the metal components in existing supported catalysts are dispersed on the surface of the carrier, which easily causes the loss of metal components during the reaction process. Therefore, there are technical problems such as shortened catalyst service life and reduced catalytic effect. Summary of the invention

[0005] In order to solve the above technical problems, one of the purposes of the present invention is to provide a method for preparing a photocatalytic degradation catalyst of Acid Red B. During the kneading process of the catalyst, a raw silicon source used for synthesizing molecular sieves is added, and then the silicon source is hydrolyzed into viscous silica gel to bond the catalyst. At the same time, the secondary pore distribution of the molecular sieve is improved in this process.

[0006] The present invention also aims to provide a catalyst for photocatalytic degradation of Acid Red B and a method for photocatalytic degradation of Acid Red B.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] In a first aspect, the present invention provides a method for preparing a photocatalytic degradation catalyst of acid red B, comprising:

[0009] S1. Mixing SBA molecular sieve powder, a metal source, a first silicon source and an alkaline solution to obtain a mixture, and forming and drying the mixture to obtain a molecular sieve A; wherein the metal source includes at least one of a vanadium source and a titanium source;

[0010] S2. The organic template R, water, a second silicon source and an acid are mixed to obtain a solution B;

[0011] S3. Add solution B to molecular sieve A, perform hydrothermal crystallization, filter, wash, dry and calcine to obtain a photocatalytic degradation acid red B catalyst.

[0012] In the preparation method of photocatalytic degradation of acid red B provided by the present invention, the first silicon source is hydrolyzed under the action of an alkaline solution to generate a viscous silica mesh, and the viscous silica mesh bonds the molecular sieve particles to each other. After extrusion molding, the viscous silica mesh is transformed into a silicon dioxide film under the condition of high temperature roasting, covering the silicon hydroxyl structure on the outer surface of the molecular sieve. Due to the silicon dioxide film and the skeleton structure silicon oxygen structure type of the molecular sieve itself, the outer surface of the molecular sieve is not covered and blocked. In practical applications, the reactants will enter the outer surface of the molecular sieve from the silicon dioxide film in the form of diffusion. However, due to the metal distribution on the outer surface of the molecular sieve, the silicon dioxide film formed will have a gap at the position of the metal, and hydrothermal crystallization is carried out by adding a mixed solution of an organic template agent R, water, a second silicon source and an acid, and the position of the gap is crystallized and grown to form a complete silicon dioxide film on the outer surface of the molecular sieve. These silicon dioxide films can improve the mechanical strength of the molecular sieve and provide a protective film for the molecular sieve structure itself. Since this protective film is similar to the silicon dioxide structure of the molecular sieve skeleton structure, it will not affect the activity and diffusion performance of the molecular sieve itself, and it can also make the metal active sites difficult to lose during the reaction process, effectively extending the life and activity of the catalyst. In addition, the silicon dioxide film formed on the outer surface of the molecular sieve can also effectively avoid the problem of metal particles agglomerating at high temperatures and causing catalyst deactivation.

[0013] According to some embodiments of the present invention, the vanadium source includes one or more of vanadium oxide, vanadic acid, and vanadate; and / or the titanium source includes one or more of titanium oxide, titanium-containing intermetallic compound, titanium-containing halide, titanium-containing inorganic salt, and titanium-containing organic salt.

[0014] According to some embodiments of the present invention, the SBA molecular sieve raw powder includes SBA-15 molecular sieve raw powder or SBA-16 molecular sieve raw powder.

[0015] According to some embodiments of the present invention, the first silicon source includes at least one of tetraethyl orthosilicate (TEOS), silica sol, and water glass, preferably tetraethyl orthosilicate.

[0016] According to some embodiments of the invention, the base in the alkaline solution comprises NaOH.

[0017] According to some embodiments of the present invention, the organic template R includes at least one of an amphiphilic nonionic triblock surfactant and hexamethylenetetramine (HMTA).

[0018] According to some embodiments of the present invention, the amphiphilic nonionic triblock surfactant comprises F127 (EO 106 PO 70 EO 106 )、F108(EO 132 PO 50 EO 132 )、P123(EO 20 PO 70 EO 20 )、P104(EO 27 PO 61 EO 27 ) at least one of.

[0019] According to some embodiments of the present invention, when the SBA molecular sieve raw powder is SBA-15 molecular sieve raw powder, the organic template R is selected from one or more of P123 or P104; when the SBA molecular sieve raw powder is SBA-16 molecular sieve raw powder, the organic template R is selected from one or more of F127, F108 and HMTA.

[0020] According to some embodiments of the present invention, the second silicon source includes at least one of white carbon black, tetraethyl orthosilicate (TEOS), sodium silicate, and silica sol, preferably tetraethyl orthosilicate.

[0021] According to some embodiments of the present invention, the acid includes at least one of hydrochloric acid, sulfuric acid, and nitric acid, preferably hydrochloric acid.

[0022] According to some embodiments of the present invention, the mass ratio of the metal source to the SBA molecular sieve raw powder is 1 to 10:100.

[0023] According to some embodiments of the present invention, the mass ratio of the first silicon source to the SBA molecular sieve raw powder is 1:5-10.

[0024] According to some embodiments of the present invention, the alkali solution contains OH - The ratio of the molar amount of the base calculated as SiO2 to the molar amount of the first silicon source calculated as SiO2 is 0.5 to 4:1.

[0025] According to some embodiments of the present invention, the alkali solution contains OH - The ratio of the molar amount of the base calculated as SiO2 to the molar amount of the first silicon source calculated as SiO2 is 0.5 to 3.5:1.

[0026] According to some embodiments of the present invention, the molar ratio of the components in the solution B is SiO2:a H2O:b R:c H + , wherein the value of a is 80 to 200, preferably 100 to 160, the value of b is 0.005 to 0.030, preferably 0.010 to 0.025, and the value of c is 0.10 to 0.25, preferably 0.15 to 0.20.

[0027] According to some embodiments of the present invention, the mixture in step S1 is first dried, and then the dried mixture is mixed with water and molded.

[0028] According to some embodiments of the present invention, the mass of water mixed with the dried mixture is 10% to 30%, preferably 15% to 25% of the mass of the dried mixture.

[0029] According to some embodiments of the present invention, the drying temperature in step S1 is 100-140°C, preferably 110-130°C.

[0030] According to some embodiments of the present invention, the crystallization temperature in step S3 is 80 to 130° C., preferably 90 to 120° C.; the crystallization time is 24 to 90 hours, preferably 40 to 70 hours.

[0031] According to some embodiments of the present invention, the drying temperature in step S3 is 100-140°C, preferably 110-130°C.

[0032] According to some embodiments of the present invention, the calcination temperature in step S3 is 400-700° C., preferably 500-600° C.; and the calcination time is 5-8 hours.

[0033] In a second aspect, the present invention provides a photocatalytic degradation catalyst for acid red B, which is prepared by the preparation method described in the first aspect.

[0034] According to some embodiments of the present invention, the surface of the photocatalytic degradation of acid red B catalyst comprises a silicon dioxide shell layer, and preferably the particle diameter of the photocatalytic degradation of acid red B catalyst is 80 to 140 nm.

[0035] In a third aspect, the present invention provides a method for photocatalytic degradation of Acid Red B, which is prepared by the preparation method described in the first aspect or catalyzed by the photocatalytic degradation of Acid Red B catalyst described in the second aspect.

[0036] The beneficial effects of the present invention are at least:

[0037] The preparation method of the photocatalytic degradation acid red B catalyst provided by the present invention is simple, a metal source is directly added in the molecular sieve forming stage, the molecular sieve does not need to be impregnated with a metal solution, and the forming and metal loading processes are completed in one step; the prepared metal-loaded SBA molecular sieve is covered with a silicon dioxide film outside the molecular sieve, which provides a protective film for the structure of the molecular sieve itself, so that the metal active sites are not easy to lose during the reaction process, and the life and activity of the catalyst are effectively extended. The catalyst is used in the complete oxidation reaction of benzene, and the degradation efficiency of acid red B can be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a scanning electron microscope image of the catalyst prepared in Example 4;

[0039] Figure 2 This is the XPS graph of the titanium atom of the catalyst prepared in Example 4. DETAILED DESCRIPTION

[0040] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.

[0041] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0042] Among them, XPS uses Thermo's ESCALAB 250spectrometer X-ray photoelectron spectrometer to measure the bonding of metal particles.

[0043] The scanning electron microscope used was Hitachi S-4700 scanning electron microscope.

[0044] The photocatalytic degradation performance was determined using an XPA-Ⅱ photoreactor produced by Nanjing Xujiang Electromechanical Plant, and the absorbance was determined using a TU-1810 UV-visible spectrophotometer produced by Beijing Puxi General Instrument Co., Ltd.

[0045] Example 1

[0046] S1. Add 40g of SBA-16 molecular sieve powder, 0.8g of sodium pyrovanadate, 4g of tetraethyl orthosilicate (TEOS) and 0.3L of 0.1mol / L NaOH solution into a mortar and mix them. After mixing evenly, dry them at 100°C. Then take 30g of the dried sample and put it into an extruder. Add 3g of deionized water and stir evenly to start molding. The molded molecular sieve is dried at 100°C and recorded as molecular sieve A.

[0047] S2. 1.6 g F127 and 34.5 g deionized water were added to the reactor in sequence, stirred evenly, and then 24.1 mL 0.1 mol / L hydrochloric acid solution was added. Stirring was continued, and 5 g tetraethyl orthosilicate (TEOS) was slowly added dropwise to obtain solution B. The molar ratio of each component in solution B was SiO2: 80H2O: 0.005R: 0.1H + .

[0048] S3. After mixing solution B and molecular sieve A, transfer them to a crystallization kettle, raise the temperature to 90°C, and crystallize at a constant temperature for 40 hours. After the crystallization is complete, wait for the temperature to drop to room temperature, separate and wash the reaction mixture, dry it at 100°C, and finally calcine it at 400°C for 8 hours to obtain the catalyst sample.

[0049] Example 2

[0050] S1. Add 40g of SBA-16 molecular sieve powder, 1.6g of sodium orthovanadate, 6g of silica sol (SW-25, with a silicon dioxide content of 25wt%) and 0.3L of 0.1mol / L NaOH solution into a mortar and mix them. After mixing evenly, dry them at 100°C. Then take 30g of the dried sample and put it into an extruder. Add 6g of deionized water and stir evenly before starting to shape it. Dry the formed molecular sieve at 100°C and record it as molecular sieve A.

[0051] S2. 4.4 g F108 and 54 g deionized water were added to the reactor in sequence, stirred evenly, and then 44.8 mL 0.1 mol / L sulfuric acid solution was added, stirring was continued, and 2 g white carbon black (silicon dioxide content was 90 wt%) was slowly added dropwise to obtain solution B. The molar ratio of each component in solution B was SiO2: 100H2O: 0.01R: 0.15H + .

[0052] S3. After mixing solution B and molecular sieve A, transfer them to a crystallization kettle, raise the temperature to 100°C, and crystallize at a constant temperature for 50 hours. After the crystallization is complete, wait for the temperature to drop to room temperature, separate and wash the reaction mixture, dry it at 110°C, and finally calcine it at 500°C for 6 hours to obtain the catalyst sample.

[0053] Example 3

[0054] S1. Add 40g of SBA-16 molecular sieve powder, 3.2g of ammonium metavanadate, 6g of tetraethyl orthosilicate (TEOS) and 0.15L0.1mol / L NaOH solution into a mortar and mix them. After mixing evenly, dry them at 100°C. Then take 30g of the dried sample and put it into an extruder. Add 7.5g of deionized water and stir evenly to start molding. The molded molecular sieve is dried at 100°C and recorded as molecular sieve A.

[0055] S2. 0.15 g of hexamethylenetetramine (HMTA) and 82.5 g of deionized water were added to the reactor in sequence, stirred evenly, and then 83 mL of 0.1 mol / L nitric acid solution was added. Stirring was continued, and 10 g of silica sol (SW-25, with a silicon dioxide content of 25 wt%) was slowly added dropwise to obtain solution B. The molar ratio of each component in solution B was SiO2: 110H2O: 0.025R: 0.2H + .

[0056] S3. After mixing solution B and molecular sieve A, transfer them to a crystallization kettle, raise the temperature to 110°C, and crystallize at a constant temperature for 60 hours. After the crystallization is complete, wait for the temperature to drop to room temperature, separate and wash the reaction mixture, dry it at 120°C, and finally calcine it at 550°C for 7 hours to obtain the catalyst sample.

[0057] Example 4

[0058] S1. Add 40g of SBA-15 molecular sieve powder, 3.2g of tetrabutyl titanate, 6g of tetraethyl orthosilicate (TEOS) and 0.3L0.1mol / L NaOH solution into a mortar and mix them. After mixing evenly, dry them at 130°C. Then take 30g of the dried sample and put it into an extruder. Add 7.5g of deionized water and stir evenly before starting to shape it. Dry the formed molecular sieve at 130°C and record it as molecular sieve A.

[0059] S2. 4.2 g P104 and 38.9 g deionized water were added to the reactor in sequence, stirred evenly, and then 60 mL hydrochloric acid solution (0.1 mol / L) was added. Stirring was continued, and 5 g tetraethyl orthosilicate (TEOS) was slowly added dropwise to obtain solution B. The molar ratio of each component in solution B was SiO2: 90H2O: 0.03R: 0.25H+ .

[0060] S3. After mixing solution B and molecular sieve A, transfer them to a crystallization kettle, raise the temperature to 130°C, and crystallize at a constant temperature for 90 hours. After the crystallization is complete, wait for the temperature to drop to room temperature, separate and wash the reaction mixture, dry it at 130°C, and finally calcine it at 400°C for 8 hours to obtain the catalyst sample.

[0061] The scanning electron microscopy images of the obtained catalyst samples are shown in Figure 1 The XPS graph of the titanium atom state analysis of the obtained catalyst sample is shown in Figure 2 .Depend on Figure 1 and Figure 2 It can be seen that the metal in the catalyst obtained by the present invention is in the form of oxide (the peak of XPS titanium dioxide is 458.5 eV) on the outer surface of the molecular sieve. Figure 2 It can be clearly seen that the outer surface is a silica spherical film and no metal oxide can be seen in the entire field of view, indicating that the metal oxide is on the outer surface of the molecular sieve inside the membrane, and the outer surface of the metal oxide is protected by a silica film, making it difficult for the metal on the outer surface of the molecular sieve to be lost during the reaction, thereby extending the service life of the catalyst.

[0062] Comparative Example 1

[0063] 40g SBA-15 molecular sieve powder and 14.2g pseudo-boehmite (Al2O3 content is 70wt%) are added to a mixer and mixed. After mixing evenly, 25.8g dilute nitric acid (HNO3 content is 6.3wt%) is added for kneading, and then 15.5g deionized water is added for further kneading. The kneaded material is then put into an extruder for molding. The molded molecular sieve is dried at 130°C and then calcined at 400°C for 8h. The molded molecular sieve sample is then mixed with 3.2g tetrabutyl titanate solution for 4h, dried at 130°C and then calcined at 400°C for 8h to obtain a Ti / SBA-15 catalyst sample.

[0064] Comparative Example 2

[0065] S1. Add 40g of SBA-15 molecular sieve powder, 3.2g of tetrabutyl titanate, 6g of tetraethyl orthosilicate (TEOS) and 2.1L 0.1mol / L NaOH solution into a mortar and mix them. After mixing evenly, dry them at 130°C. Then take 30g of the dried sample and put it into an extruder. Add 7.5g of deionized water and stir evenly before starting to shape it. The formed molecular sieve is dried at 130°C and recorded as molecular sieve A.

[0066] S2. 4.2 g P104 and 38.9 g deionized water were added to the reactor in sequence, stirred evenly, and then 60 mL hydrochloric acid solution (0.1 mol / L) was added. Stirring was continued, and 5 g tetraethyl orthosilicate (TEOS) was slowly added dropwise to obtain solution B. The molar ratio of each component in solution B was SiO2: 90H2O: 0.03R: 0.25H + .

[0067] S3. After mixing solution B and molecular sieve A, transfer them to a crystallization kettle, raise the temperature to 130°C, and crystallize at a constant temperature for 90 hours. After the crystallization is complete, wait for the temperature to drop to room temperature, separate and wash the reaction mixture, dry it at 130°C, and finally calcine it at 400°C for 8 hours to obtain the catalyst sample.

[0068] Catalytic effect evaluation

[0069] The catalyst samples prepared in the embodiments and comparative examples were used in the experiment of photocatalytic degradation of Acid Red B, and the specific process was as follows:

[0070] Using deionized water as solvent, prepare a 50 mg / L acid red B solution as simulated wastewater. Take 400 mL of the reaction solution and place it in a photoreactor, add 0.1 g / L of catalyst. Irradiate with a 300W medium-pressure mercury lamp, the emission wavelength range of the mercury lamp is 250-720 nm, the main wavelength is 365 nm, and the light intensity of the mercury lamp at 365 nm is 0.19 kW / m 2 After irradiation for 120 minutes, when the photocatalytic reaction reached equilibrium, a sample was taken, the suspension was centrifuged (3500r / min, 30min), the supernatant was taken, and the absorbance of Acid Red B at its maximum absorption wavelength of 518nm was measured by UV-visible spectrophotometer to evaluate the photocatalytic degradation activity of Acid Red B on the catalyst. The test results are shown in Table 1.

[0071] Table 1

[0072] Acid Red B removal rate (%) Example 1 98.2 Example 2 98.6 Example 3 98.9 Example 4 99.5 Comparative Example 1 75.7 Comparative Example 2 25.0

[0073] It can be seen from the above test results that the catalysts prepared by the preparation method provided by the present invention in Examples 1-4 show excellent catalytic performance in terms of acid red B removal rate.

[0074] Comparative Example 1 uses a traditional loading impregnation method. Firstly, due to the addition of adhesives during the molding process, the traditional method has relatively fewer active sites in the catalyst of the same mass. Secondly, due to the lack of protection of the outer surface silica film, the metals on the surface of these molecular sieves are very likely to be lost during the reaction, resulting in a decrease in catalyst activity.

[0075] In Comparative Example 2, due to the addition of too much alkali, the framework of the molecular sieve itself will collapse while the silicon source is hydrolyzed to form a silicon dioxide film and a sticky network, so the catalytic activity is very low.

[0076] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A method for preparing a photocatalytic degradation catalyst for acid red B, characterized in that: The following steps are involved: S1. Mixing SBA molecular sieve powder, a metal source, a first silicon source and an alkaline solution to obtain a mixture, and forming and drying the mixture to obtain a molecular sieve A; wherein the metal source includes at least one of a vanadium source and a titanium source; S2. The organic template R, water, a second silicon source and an acid are mixed to obtain a solution B; S3. Add solution B to molecular sieve A, perform hydrothermal crystallization, filter, wash, dry and calcine to obtain a photocatalytic degradation catalyst for acid red B.

2. The preparation method according to claim 1, characterized in that: The vanadium source includes one or more of vanadium oxide, vanadic acid, and vanadate; and / or the titanium source includes one or more of titanium oxide, titanium-containing intermetallic compound, titanium-containing halide, titanium-containing inorganic salt, and titanium-containing organic salt.

3. The preparation method according to claim 1 or 2, characterized in that: The SBA molecular sieve raw powder includes SBA-15 molecular sieve raw powder or SBA-16 molecular sieve raw powder; and / or, the first silicon source comprises at least one of tetraethyl orthosilicate, silica sol, and water glass, preferably tetraethyl orthosilicate; And / or, the alkali in the alkali solution comprises NaOH.

4. The preparation method according to any one of claims 1 to 3, characterized in that The organic template R comprises at least one of an amphiphilic nonionic triblock surfactant and hexamethylenetetramine; And / or, the second silicon source includes at least one of white carbon black, tetraethyl orthosilicate, sodium silicate, and silica sol; And / or, the acid includes at least one of hydrochloric acid, sulfuric acid, and nitric acid.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The amphiphilic nonionic triblock surfactant includes at least one of F127, F108, P123, and P104; And / or, the second silicon source is tetraethyl orthosilicate; And / or, the acid is hydrochloric acid.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The mass ratio of the metal source to the SBA molecular sieve raw powder is 1 to 10:100; And / or, the mass ratio of the first silicon source to the SBA molecular sieve raw powder is 1:5-10; And / or, the alkaline solution contains OH - The ratio of the molar amount of the base calculated as SiO2 to the molar amount of the first silicon source calculated as SiO2 is 0.5 to 4:1, preferably 0.5 to 3.5:

1.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The molar ratio of each component in the solution B is SiO2:a H2O:b R:c H + , wherein the value of a is 80 to 200, preferably 100 to 160, the value of b is 0.005 to 0.030, preferably 0.010 to 0.025, and the value of c is 0.10 to 0.25, preferably 0.15 to 0.

20.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The mixture in step S1 is first dried, and then the dried mixture is mixed with water and then formed; Preferably, the mass of water mixed with the dried mixture is 10% to 30%, preferably 15% to 25% of the mass of the dried mixture.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The drying temperature in step S1 is 100-140°C, preferably 110-130°C; And / or, the crystallization temperature in step S3 is 80-130° C., preferably 90-120° C.; the crystallization time is 24-90 hours, preferably 40-70 hours; And / or, the drying temperature in step S3 is 100-140° C., preferably 110-130° C.; And / or, the calcination temperature in step S3 is 400-700° C., preferably 500-600° C.; and the calcination time is 5-8 hours.

10. A photocatalytic degradation of acid red B catalyst, prepared by the preparation method according to any one of claims 1 to 9, wherein the surface of the photocatalytic degradation of acid red B catalyst comprises a silicon dioxide shell layer, and preferably the particle diameter of the catalyst is 80 to 140 nm.

11. A method for photocatalytic degradation of Acid Red B, wherein the reaction is catalyzed by the catalyst prepared by the preparation method according to any one of claims 1 to 9 or the catalyst according to claim 10.

Citation Information

Patent Citations

  • Silicon modified core-shell molecular sieve and preparation method thereof

    CN103539152A

  • Load type metal mesoporous molecular sieve noble metal catalyst and preparation method thereof

    CN104857983A

  • Preparation method and application of manganese-doped 4A molecular sieve

    CN110201632A

  • Preparation method and application of core-shell type metal zeolite catalyst

    CN112844456A

  • Method for obtaining metal oxides supported on mesoporous silica particles

    CN113874318A